The effect of whey protein on malondialdehyde, aerobic capacity, and leg muscle explosive power in basketball athletes - Novia Arista; M Zen Rahfiludin; Ali Rosidi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: High-physical activity, including aerobic capacity and leg muscle explosive power, can cause stress oxidative and decrease the performance of athletes. Whey protein contains essential amino acids that were beneficial to decreased malondialdehyde (MDA) levels.Objective: To analyze the effect of whey protein on MDA level, aerobic capacity, and leg muscle explosive power in basketball athletes.Materials and Methods: Randomized controlled trial using pre- and post-test design was conducted on 12 male athletes aged 16-18 years at PPLOP Central Java Basketball Club. The treatment group received 30 grams of whey protein, and the control group received 30 grams of chocolate powder as a placebo for 28 days. MDA levels were measured through Elisa methods. Aerobic capacity was measured by 20 meters sprint. Leg muscle explosive power was measured by vertical jump. Data were analyzed by an independent t-test.Results: The mean MDA levels before intervention in the whey protein group were 182.36 (±59.05), and the mean after the intervention was 171.83 (±5.46). The mean before the aerobic intervention capacity was 36.95 (±5.84), and the mean after the intervention was 49.75 (±3.53). The mean leg muscle explosive was 83.50 (±21.58), and the mean after the intervention was 87.33 (±16.68). There were no effect of whey protein on MDA levels (p>0,05), aerobic capacity (p>0,05) and leg muscle explosive power (p>0,05).Conclusion: Whey protein for 28 days had no effect on MDA levels, aerobic capacity, and leg muscle explosive power